The Propositional Evaluation Paradigm: Indirect Assessment of Personal Beliefs and Attitudes - Müller, Florian; Rothermund, Klaus (Frontiers in Psychology, 2019)
Identification of propositions as the core of attitudes and beliefs (De Houwer, 2014) has resulted in the development of implicit measures targeting personal evaluations of complex sentences (e.g., the IRAP or the RRT). Whereas their utility is uncontested, these paradigms are subject to limitations inherent in their block based design, such as allowing assessment of only a single belief at a time. We introduce the Propositional Evaluation Paradigm (PEP) for assessment of multiple propositional beliefs within a single experimental block. Two experiments provide first evidence for the PEP’s validity. In Experiment 1 endorsement of racist beliefs measured with the PEP was related to criterion variables such as explicit racism assessed via questionnaire and indicators of behavioral tendencies. Experiment 2 indicates that the PEP’s implicit racism scores may predict actual behavior over and above explicit, self-report measures. Finally, Experiment 3 tested the PEP's applicability in the domain of hiring discrimination. Whereas general PEP based gender stereotypes were not related to hiring bias, results suggest a possible role of female stereotypes in hiring discrimination. In the context of these findings, we discuss both the potential and possible challenges in adopting the PEP to different beliefs. In sum, these initial findings suggest that the PEP may offer researchers a reliable and easily administrable option for the indirect assessment of propositional evaluations.